PENGARUH KINERJA KEUANGAN PERUSAHAAN TERHADAP RETURN SAHAM (Studi Pada Perusahaan Food and Beverages yang Terdaftar di BEI) - Putri, Ayu Kemala (Arthavidya Jurnal Ilmiah Ekonomi, 2016)
Abstrack, The existence of capital markets can provide benefits to allparties involved in capital market activities. The existence of capitalmarket specifically benefit the two parties who have excess funds(investors) and those who need the funds (issuer) The aim of thisstudy to determine the effect Earning Per Share (EPS), Price EarningRatio (PER), Debt to Equity Ratio (DER) , return on Equity (ROE)and Economic Value Added (EVA) to return stock at the company’sFood and Beverages. Result, that of simultaneous these variablesdid not have a significant influence. Partially, only variable Debt toEquity Ratio (DER) has significant influence on stock returns.Keywords: Earning Per Share (EPS), Price Earning Ratio (PER),Debt to Equity Ratio (DER), Return on Equity (ROE),Economic Value Added (EVA)